2011
DOI: 10.1007/s10705-011-9465-x
|View full text |Cite
|
Sign up to set email alerts
|

Field-specific simulations of net N mineralization based on digitally available soil and weather data: II. Pedotransfer functions for the pool sizes

Abstract: Avoiding surplus N fertilization without reducing crop yields could be accomplished by accounting for current net N mineralization in N fertilizer recommendations. N simulation models would allow a quantitative consideration of important factors and could be based upon digitally mapped data. Soil-specific temperature and water functions that were derived in part I of the paper needed a differentiation between only three soil groups and the two allocating criteria were taken from digital soil maps. Here, the ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…A requirement for these simulations is that specific functions, e.g. pedotransfer functions for the pool sizes of mineralizable soil organic N, are derived by only using data from digital soil maps instead of measured data (Heumann et al 2011a(Heumann et al , 2011b.…”
Section: Methodsmentioning
confidence: 99%
“…A requirement for these simulations is that specific functions, e.g. pedotransfer functions for the pool sizes of mineralizable soil organic N, are derived by only using data from digital soil maps instead of measured data (Heumann et al 2011a(Heumann et al , 2011b.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Heumann et al (2003) found that the size of the N slow pool of a two-pool first-order kinetic equation can be accurately derived from one or two basic soil characteristics when the sites are grouped by former land-use. Heumann et al (2011) successfully derived pedotransfer functions for predicting the N slow and N fast pool sizes from a two-pool first-order kinetic model using either digitally available or measured soil characteristics. The results of this present study indicate that the depth distribution of soil mineralizable N pools can vary substantially among sites under the semi-arid environment in western Canada.…”
Section: Interactions Between Mineralizable N Pools and Soil Propertiesmentioning
confidence: 99%
“…However, the depth considered in kinetic models used to predict net N mineralization varies widely. For example, Stanford et al (1977) considered a depth of 0-45 cm; Marion et al (1981) considered depths ranging from 0-13 cm to 0-44 cm, depending on the soil and horizon used; Griffin and Laine (1983) considered the depth of the Ap horizon, which varied with the soil; Cabrera and Kissel (1988) considered a depth of 120 cm, with 15 and 30 cm depth increments; Mikha et al (2006) assumed that the 0-5 cm depth mineralizable N was representative of the 0-30 cm depth considered in their model; and Heumann et al (2002Heumann et al ( , 2011 considered a depth of 28-30 cm. DessureaultRompré et al (2011DessureaultRompré et al ( , 2012) used a kinetic model to predict field-measured soil N supply, and obtained better prediction when using a soil depth of 0-20 or 0-30 cm than when using 0-15 cm.…”
Section: Introductionmentioning
confidence: 99%
“…Although we are not aware of previous attempts to predict the mineralizable N parameters of a model such as the zero-plus first-order model, others have attempted to predict the mineralizable N parameters of the two pool model where both pools have first-order kinetics. Heumann et al (2011) derived pedotransfer functions for predicting N slow and N fast pool sizes from a two-pool two-first-order kinetic model using either digitally available or measured soil characteristics. The study included 179 arable soils from Lower Saxony in northwestern Germany with a broad range of soil properties.…”
Section: Prediction Of N 0 From Soil Mineralizable N Pools and Soil Pmentioning
confidence: 99%
“…Similarly, Heumann et al (2003) found the size of the N slow pool of a two-pool first-order kinetic equation can be accurately derived from one or two basic soil characteristics when the sites are grouped by former land-use. More recently, Heumann et al (2011) successfully derived pedotransfer functions for predicting the N slow and N fast pool sizes from a two-pool two-first-order kinetic model using either digitally available or measured soil characteristics. The first objective of this study was to develop regression equations to predict the mineralizable N parameters obtained from fitting first-order (i.e., Eq.…”
mentioning
confidence: 99%